Radiation hardness of the LHCb Outer Tracker - Eijk, Daan van; Bachmann, Sebastian; Färber, Christian; Bien, Alexander; Gersabeck, Evelina; Langenbruch, Christoph; Linn, Christian; Meißner, Marco; Seyfert, Paul; Uwer, Ulrich; Wiedner, Dirk (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2012)
This paper presents results on the radiation hardness of the LHCb Outer Tracker (OT) during LHC operation in 2010 and 2011. Modules of the OT have shown to suffer from ageing effects that lead to gain loss, after irradiation in the laboratory. Under irradiation at moderate intensities an insulating layer is formed on the anode wire of the OT straw cells. This ageing effect is caused by contamination of the counting gas due to outgassing of the glue used in the construction of the OT modules. Two methods to monitor gain stability in the OT are presented: module scans with radioactive sources and the study of hit efficiency as a function of amplifier threshold. No gain loss is observed after receiving 1.3fb−1 of integrated luminosity corresponding to an integrated charge of 0.055C/cm in the hottest spot of the detector.